Drugs susceptibility testing of mycobacterium tuberculosis using direct tetrazolium microplate assay (TEMA) - Yahaya, Mohammad Lukman (2015)
A rapid, inexpensive and high-throughput assay for drug susceptibility testing (DST) of Mycobacterium tuberculosis (MTB) is urgently required especially in developing countries where TB cases are prevalent. The aim of this study was to evaluate the drug susceptibility testing (DST) of MTB to the first-line anti-TB drug using tetrazolium microplate assay (direct TEMA) performed directly on clinical specimens (sputum) by omitting the need for prior isolation of MTB in sputum specimens currently performed by indirect TEMA. A total of 59 acid fast bacilli (AFB) smear positive sputum specimens were directly inoculated into drug-free and serially diluted drug in 7H9-S broth media using tetrazolium dye as growth indicator in the microplate wells. All AFB smear categories with different microscopic bacilli counts (from scanty to 3+) were included in the direct TEMA while the standard inoculum size used in the indirect TEMA was 1.50 × 107 CFU/mL. The minimum inhibitory concentrations (MICs) of isoniazid (INH), rifampicin (RMP), ethambutol (EMB) and streptomycin (SM) were obtained for direct and indirect TEMA with reference to the absolute concentration method (ACM). Receiver Operating Characteristics (ROC) curve was used to determine the cut-off MIC values. The sensitivity, specificity, accuracy and predictive values as well as the mean turnaround time (TAT) for the final sensitivity test results were compared. The MIC for more than 70% of MTB strains were distributed between 0.0156 to 0.0313 μg/mL for INH; 0.0005 to 0.25 μg/mL for RMP; 0.5 to 2.0 μg/mL for EMB and 0.0625 to 0.25 μg/mL for SM for indirect TEMA whereas 0.0039 to 0.0625 μg/mL for both INH and RMP; 0.25 to 1.0 μg/mL for EMB and 0.0625 to 0.25 μg/mL for SM for direct TEMA. The direct TEMA method performed well by accurately distinguishing between the resistant and susceptible strains of MTB as seen by the area under the ROC curve (AUC) ranged from 0.7569 to 0.9643 against the first-line anti-TB drugs. In indirect TEMA, 80%, 71%, 75% and 100% sensitivities were obtained for INH, RMP, EMB and SM respectively while specificities were 96%, 60%, 38% and 84% for INH, RMP, EMB and SM respectively. In the direct TEMA, 100% sensitivity was obtained for INH, EMB and SM and 71% for RMP. However, the specificities for INH, RMP, EMB and SM were 80%, 71%, 55% and 93% respectively. The overall accuracy and predictive values of direct TEMA were comparable to indirect TEMA. A significant shorter mean TAT of 15 days was observed for direct TEMA followed by indirect TEMA (39 days) and ACM (100 days) (P < 0.001). In conclusion, direct TEMA is a relatively simple, rapid and reliable method for DST screening of MTB in countries with increasing prevalence rates of drug resistance strains.